High rates of therapeutic changes in patients with psoriatic arthritis receiving treatment with disease-modifying antirheumatic drugs: a cross-sectional study - Behrens, Frank; Rech, Jürgen; Thaçi, Diamant; Zinke, Silke; Rothnie, Kieran J.; Oefner Daamen, Carolin; Leipe, Jan (Modern rheumatology, 2022)
To characterize treatment patterns for patients with psoriatic arthritis (PsA) currently receiving any disease-modifying antirheumatic drug (DMARD).The Strategy for Psoriatic Arthritis In Germany (SPAIG) study was a retrospective observational study conducted from May to November 2017 at 46 rheumatology centers. Current and previous treatment data were collected at a single visit from adult patients with PsA and psoriasis who received DMARD treatment for ≥6 of the previous 12 months. The primary outcome was the proportion of patients receiving a biologic DMARD (bDMARD). Multinomial logistic regression analysis was used to evaluate associations between current characteristics and initial choice of therapy.Mean age of the 316 patients was 55.1 years and mean PsA disease duration was 9.9 years. PsA activity was generally comparable across treatment groups. In this cohort, 57.3% of patients were currently treated with bDMARDs, 37.7% with conventional synthetic DMARDs, and 4.4% with targeted synthetic DMARDs. Almost half (48.4%) of patients reported DMARD modifications in the previous 12 months. Specific comorbidities and patient/disease characteristics were associated with initial therapy.DMARD treatment of PsA is frequently modified, suggesting the need for more effective therapies and assessment tools.
Gesehen am 06.12.2022